2011
DOI: 10.1038/pj.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel transitions of poly(vinylidene fluoride) in organic solvents containing LiBF4

Abstract: Poly(vinylidene fluoride) (PVdF) dissolved in organic solvents containing lithium tetrafluoroborate (LiBF 4 ) forms stable gels when the solution is cooled to room temperature. Here, we describe the effects of LiBF 4 concentration and different gelation solvents on the gelation process, and characterize the resulting structural morphology using several techniques. Diethyl carbonate (DEC), propylene carbonate (PC) and c-butyrolactone (GBL) were used as gelation solvents. Time-resolved Fourier transform infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…While at the presence of polar solvent in typical aqueous solution, the solvent molecules solvated the ions can screen the interaction among the ions and thus lower the Q* value and thus the Seebeck coefficient. [38][39][40][41] The structures of α, β, and amorphous PVDF-HFP are shown in Figure S9 the neat PVDF-HFP film. [11] The solvent screening is weak when the solvent is less polar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While at the presence of polar solvent in typical aqueous solution, the solvent molecules solvated the ions can screen the interaction among the ions and thus lower the Q* value and thus the Seebeck coefficient. [38][39][40][41] The structures of α, β, and amorphous PVDF-HFP are shown in Figure S9 the neat PVDF-HFP film. [11] The solvent screening is weak when the solvent is less polar.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the ion‐dipole interactions, the Fourier‐transform infrared spectroscopy (FTIR) spectra of different ionogels were measured ( Figure 3 a). For the neat PVDF‐HFP film by spin coating, the FTIR bands at 491(δCF 2 ), 533(δCF 2 ), 614(δCF 2 + δskeleton), 761(δCF 2 + δskeleton), and 797 cm −1 (ρCH 2 ) can be assigned to the α phase of PVDF‐HFP, and the band at 875 cm −1 (ρCH 2 ) is due to amorphous structure of PVDF‐HFP . The structures of α, β, and amorphous PVDF‐HFP are shown in Figure S9 (Supporting Information).…”
Section: Discussionmentioning
confidence: 99%
“…PVDF-HFP has a slight interaction with DEC and is, thus, considered as a gelation solvent [37]. DEC can wash away the CB clumps or interact with the small amount of oxygen groups on CB.…”
Section: Methodsmentioning
confidence: 99%
“…The crystallinity of the gel is expected to be associated with the crystallinity of the constituent polymer because the PVDF-based gel formation includes the same crystal precipitation and growth process, as in the case of the solid polymer . In practice, it has been reported that the size of the polymer spherulites of the PVDF-based gel electrolytes observed via scanning electron microscopy (SEM), which reflects the crystallinity of the gel, depends on the type of solvent, salt concentration, and cooling conditions for gelation. , Although SEM observations provide direct information on the size of the crystal, in practice, it is difficult to evaluate the morphology of the gel under the equilibrium state from SEM images. This is because the morphology and composition of a gel sample can easily change in the evacuated space of the SEM equipment, as it consists of a mixed system of a solid polymer and a liquid electrolyte solution.…”
Section: Introductionmentioning
confidence: 99%